Rapid development and rupture of a pulmonary cyst in the early postoperative period after pulmonary resection: A case report. Issue 6 (4th April 2020) - Kawamoto, Nobutaka; Okita, Riki; Hayashi, Masataro; Furukawa, Masashi; Inokawa, Hidetoshi; Okabe, Kazunori
Abstract: Air leakage is a common complication after pulmonary resection, which is usually caused by direct lung damage during surgery. Herein, we describe a case in which a pulmonary cyst developed rapidly in the right lower lobe and ruptured 10 days after right upper lobectomy. A 49‐year‐old man, who was a heavy smoker, underwent thoracoscopic right upper lobectomy for primary lung cancer. No air leakage was observed postoperatively, and the chest drain tube was removed on postoperative day 1. Although his postoperative course was uneventful for more than a week, extensive subcutaneous emphysema developed unexpectedly on postoperative day 10. Computed tomography (CT) scan revealed a large pulmonary cyst in the right lower lobe that was not present before the right upper lobectomy. Surgery was performed on postoperative day 13, and it revealed a large thick‐walled pulmonary cyst in the right lower lobe. The cyst was filled with blood clots, and air leaks were observed inside it, suggesting that the dissection of the pulmonary parenchyma caused its development. The cyst wall was sutured together with the pulmonary parenchyma, and no air leakage was subsequently observed. Key points: Significant findings of the study In patients with fragile pulmonary tissue, the pulmonary parenchyma may become dissociated after pulmonary resection and induce rapid development of a pulmonary cyst. Risk factors for pulmonary cyst development include upper lobectomy and emphysema. Pulmonary cysts are often formed in the lower lobe. What this study adds In patients with pulmonary emphysema post‐upper lobectomy, the fragility of the pulmonary parenchyma and hyperinflation of the remaining lung may cause dissection of the pulmonary parenchyma, resulting in massive air leakage.